Use, practices and attitudes of elite and sub-elite athletes towards tart cherry supplementation - Wangdi, J. T.; Sabou, V.; O`Leary, M. F.; Kelly, V. G.; Bowtell, J. L. (Sports, 2021)
Tart cherry (TC) supplementation can improve exercise recovery and performance; and may also improve sleep duration and quality. This study investigated the use and knowledge of TC supplementation by athletes of all competitive levels. Eighty participants (52.5% elite (international, national, professional), 47.5% sub-elite (semi-professional, state/regional, county level, club level, recreational)) completed an online questionnaire investigating their attitudes towards and use of TC supplementation. Overall, 22.6% of participants were using or had previously used TC supplements, and 12.5% of participants planned to used TC supplements. Improved recovery (71.4%), sleep (32.1%) and immunity and general health (32.1%) were the most frequently indicated goals by respondents using TC supplements. In total, 32.1% of respondents were supplemented with TC chronically, 39.3% acutely and 28.6% used a combination of chronic and acute supplementation. The majority of those employing TC supplementation chronically used TC either over 2-3 days (37.0%) or continuously (37.0%). The most popular TC pre- and post-loading period was one day (34.3% and 41.5%, respectively). There were no significant differences between elite and sub-elite athletes in any parameters assessed (p > 0.05). TC supplementation is not widely used by the athletes surveyed, and athletes using TC supplements showed poor awareness of an evidence-led dosing strategy, regardless of competitive level.